Transkripsi Sastra Lisan Melayu Jambi sebagai Alternatif Bahan Ajar Sastra di Perguruan Tinggi - Liza Septa Wilyanti; Larlen Larlen; Sovia Wulandari (Universitas Batanghari Jambi, 2022)
The aim of the study was to transcribe Jambi Malay oral literature, especially literature in the form of prose (folklore). Jambi Malay oral literature transcription is a literary documentary research. This research is included in qualitative research with descriptive method. The data used in this study is oral literature in the form of prose (folklore). The source of data in this study is data obtained from research informants. The data was obtained through direct interviews with informants. . Interviews with informants were conducted using tapping and recording techniques. Based on the results of the analysis of the stories that have been transcribed, it was found that there are four types of stories, namely legends, fairy tales, witty stories, and myths.